Alfred Stieglitz, Camera Work. The Complete Photographs 1903-1917, Köln: Taschen Bibliotheca Universalis, 2022, 552 p. - CRĂCIUN, Maria Silvia (Studia Universitatis Babeș-Bolyai Historia Artium, 2023)
The catalogue is a new edition of the 1997 original, and frames the photographs, now owned by the Royal Photographic Society, Bath, published in Camera Work between 1903 and 1917. As such, it highlights the multifaceted work of Alfred Stieglitz (1864-1946), known first and foremost as a photographer, although he was also a publisher and curator. However, his contribution to the field of photography is not restricted to his own astounding photographs. Around the turn of the twentieth century, he founded the Photo-Secession, a progressive movement concerned with exploring the creative side of photography. This was part of Stieglitz’s plan to gain recognition for photography as an art form in its own right, propelling it from a peripheral position to center stage. In this context, in 1903, Stieglitz began publishing Camera Work, an avant-garde magazine devoted to expressing the ideas of the Photo-Secession in both images and words. Camera Work is considered the first photo journal whose focus was visual rather than technical and its illustrations were of the highest possible quality. Thus, the first merit of this book is to bring together the amazing photographs from the journal’s 50 issues while highlighting Stieglitz’s work as a publisher. As a journal, Camera Work was also intimately linked to the Little Galleries of the Photo Secession, often referred to simply as 291, for the number where they were located on Fifth Avenue, to the point of becoming an exhibition catalogue and a publicity machine for the Photo-Secession.